Spin-orbit coupling in double-sided doped InAs quantum well structures - Kim, Kyung-Ho; Kim, Hyung-jun; Koo, Hyun Cheol; Chang, Joonyeon; Han, Suk-Hee (AMER INST PHYSICS, 2010)
We have investigated Rashba spin-orbit interaction [Bychkov and Rashba, JETP Lett. 39, 78 (1984)] parameter (alpha) in double-sided doped InAs quantum well structures of different potential asymmetries created by introducing two separated carrier supply layers. The internal potential asymmetry is manipulated between negative and positive potential gradient by adjusting the relative doping concentrations of the two carrier supply layers. The larger potential asymmetry results in the more extensive variation in alpha with respect to gate electric field (V(g)). The structures of the negative and positive potential gradients exhibit the opposite variation in alpha with respect to V(g) which evidently supports the fact that the sign of alpha can be changed by the reversed potential asymmetry. (C) 2010 American Institute of Physics. [doi:10.1063/1.3462325]
Keywords: GATE CONTROL; HETEROSTRUCTURE; CHANNEL